Identifying Characteristics of Fault in Distributed Solar Generation System - Rajesh B. Mapari (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The fault current in inverter-based distributed energy resources (DERs) is very low, and there are almost no negative or zero sequence currents. For fault analysis and putting up protective relays, it's important to know how DER faults behave. Even though a lot of work has been done on modelling DER, not much has been done to look at how DER behaves during real problem events. This suggested system looks at recorded fault events that Dominion Energy has kept track of. The size, angle, and order of the fault components are looked at to show that the real DER fault reaction may be different from what was thought before. Radial lines are what most distribution feeders are, and the utility is the only source of fault current. Most of the time, overcurrent methods are used to find faults. An overcurrent device works in overcurrent schemes when the measured current goes over a certain number, either for a short time or after a delay in time. The primary and backup protective devices work together to make sure that a fault is safely fixed before the backup device starts a delay. With the rise of Distributed Energy Resources (DERs) on distribution lines, there is now another source of fault current. The fault current from DERs can partly cancel out the fault current contribution from the utility, which causes relay operations to be delayed. Because DER affects fault current, it is very important to have a good picture of how a DER fault looks for fault analysis and setting the protection relay.